Perioperative Hemodynamic Instability and Its Impact on Early Gastrointestinal Recovery Following Major Upper Abdominal Surgery in High-Risk Cardiac Patients: A Prospective Observational Study - Faisal Toheed, Rahil Mahmood ur Rahman, Fakhar Ilyas Malik, Inamullah, Imam Alam, S. Iftikhar Alam (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Perioperative hemodynamic instability is a major determinant of postoperative outcomes in high-risk cardiac patients undergoing major upper abdominal surgery. Impaired systemic and splanchnic perfusion may adversely affect gastrointestinal (GI) recovery, leading to delayed return of bowel function and increased morbidity. Objective: To evaluate the impact of perioperative hemodynamic instability on early gastrointestinal recovery in high-risk cardiac patients undergoing major upper abdominal surgery. Methods: This prospective observational study was conducted at Karachi Medical and Dental College and Mekran Medical College from June 2022 to June 2023. A total of 120 patients (ASA III–IV) undergoing elective major upper abdominal surgery were enrolled through consecutive non-probability sampling. Hemodynamic instability was defined as sustained hypotension (MAP < 65 mmHg), vasopressor requirement, or significant heart rate variability. Patients were categorized into stable and unstable groups. Primary outcomes included time to first bowel sound, passage of flatus, and tolerance of oral intake. Data were analyzed using SPSS version 26, with p < 0.05 considered significant. Results: Hemodynamic instability was observed in 43.3% of patients. The unstable group demonstrated significantly delayed first bowel sounds (37.6 ± 8.5 vs 25.3 ± 6.8 hours), delayed passage of flatus (59.8 ± 10.7 vs 42.5 ± 9.3 hours), and prolonged time to oral intake (4.9 ± 1.4 vs 3.2 ± 1.0 days) (p < 0.001). Length of hospital stay was also significantly increased (9.6 ± 2.3 vs 7.1 ± 1.8 days, p < 0.001). Hypotension (AOR = 3.12) and vasopressor use (AOR = 2.47) were independent predictors of delayed GI recovery. Conclusion: Perioperative hemodynamic instability significantly delays gastrointestinal recovery in high-risk cardiac patients. Optimizing intraoperative hemodynamic parameters may improve postoperative outcomes and reduce complications. Keywords: Hemodynamic instability, gastrointestinal recovery, perioperative hypotension, abdominal surgery, cardiac patients, postoperative ileus